Developing a method for evaluating the value of hoisting risk response strategies: a multi-stakeholder perspective - Junjia, Yin; Alias, Aidi Hizami; Haron, Nuzul Azam; Abu Bakar, Nabilah (Emerald Publishing, 2024)
Purpose: Hoisting is an essential construction work package, but there is still a high incidence of accidents due to insufficient attention to coping strategies. This study aims to provide decision support to practitioners on safety protocols by developing a multi-stakeholder risk response model and a novel evaluation method. Design/methodology/approach: Firstly, the study summarizes the hoisting risk response strategies system through a literature review and stakeholder theory. Secondly, the study constructed a quantitative theoretical model based on GLS-SEM and questionnaires. Third, the EWM-VA evaluation method was developed to determine the value coefficients of strategies. Findings: The strategic interaction between government and consultants, consultants and builders, and government and builders are in the top three pronounced. Three coping strategies, “Increase funding for lifting equipment and safety devices,” “Improve the quality of safety education and training on lifting construction,” and “Conduct regular emergency rescue drills for lifting accidents,” have the optimal ratio of benefits to costs. Originality/value: The hoisting risk strategy model from the perspective of multi-interested subjects proposed by the study is based on the global thinking of the project, which reduces the troubles such as the difficulty of pursuing responsibility and the irrational allocation of strategies that were brought by the previously related studies that only considered a single interested subject. In addition, the EWM-VA evaluation method developed in the study also provides new options for evaluating risk strategies and has the potential to be extended to other fields. © 2024, Emerald Publishing Limited.